Potential of different fluoride gels to prevent erosive tooth wear caused by gastroesophageal reflux - Philipp Körner; Luca Georgis; Daniel B. Wiedemeier; Thomas Attin; Florian J. Wegehaupt (BMC, 2021)
Abstract Background This in-vitro-study aimed to evaluate the potential of different fluoride gels to prevent gastroesophageal reflux induced erosive tooth wear. Methods Surface baseline profiles of a total of 50 bovine enamel specimens [randomly assigned to five groups (G1-5)] were recorded. All specimens were positioned in a custom made artificial oral cavity and perfused with artificial saliva (0.5 ml/min). Reflux was simulated 11 times a day during 12 h by adding HCl (pH 3.0) for 30 s (flow rate 2 ml/min). During the remaining 12 h (overnight), specimens were stored in artificial saliva and brushed twice a day (morning and evening) with a toothbrush and toothpaste slurry (15 brushing strokes). While specimens in the control group (G1) did not receive any further treatment, specimens in G2-5 were coated with different fluoride gels [Elmex Gelée (G2); Paro Amin Fluor Gelée (G3); Paro Fluor Gelée Natriumfluorid (G4); Sensodyne ProSchmelz Fluorid Gelée (G5)] in the evening for 30 s. After 20 days, surface profiles were recorded again and enamel loss was determined by comparing them with the baseline profiles. The results were statistically analysed using one-way analysis of variance (ANOVA) followed by Tukey`s HSD post-hoc test. Results The overall highest mean wear of enamel (9.88 ± 1.73 µm) was observed in the control group (G1), where no fluoride gel was applied. It was significantly higher (p < 0.001) compared to all other groups. G2 (5.03 ± 1.43 µm), G3 (5.47 ± 0.63 µm, p = 0.918) and G4 (5.14 ± 0.82 µm, p > 0.999) showed the overall best protection from hydrochloric acid induced erosion. Enamel wear in G5 (6.64 ± 0.86 µm) was significantly higher compared to G2 (p = 0.028) and G4 (p = 0.047). Conclusions After 20 days of daily application, all investigated fluoride gels are able to significantly reduce gastroesophageal reflux induced loss of enamel.